Predictors of Mental health in Pregnant Women: Application of the theory of planned behavior - Zeinab Jalambadani; Zakieh Sadat Hosseini (IP Berlin A.V., 2022)
Aim. The purpose of this study was to predictors of mental health in pregnant women based on theory of planned behavior referred to Iran health centers during the COVID-19 in 2021. Materials and methods. This study was cross-sectional study thatwas conducted on 250 pregnant women. Pregnant women completed General Health Questionnaire (GHQ) and theory of planned behavior questionnaire. The data were analyzed with SPSS software version 20 (SPSS Inc., Chicago, IL, USA) through running Pearson Correlation statistical tests, descriptive statistics methods including frequency, percentage, mean, standard deviation scores. The Kruskal-Wallis test was used for normally distributed variable. The significance level of the tests was considered to be 0.05. Results. There was a significant correlation between mental health disorders and some personal and socioeconomic factors. The findings showed that all structures attitude (r=0.69, p0.001), subjective norms (r=0.58, p0.001) and perceived behavioral control (r=0.56, p0.001) and intention (r=0.51, p0.001) had significant correlations with mental health. Among the variables entered into the regression model, attitude, subjective norms and perceived behavioral control were able to predict 65 percent of variance of mental health among the participants (F=60.75, R=0.66, R2=0.65). Conclusion. It is necessary to plan for appropriate care in order to prevent the occurrence of mental disorders among this vulnerable group.